The polygraph system as an instrument for measuring physiological reactions to advertisement - Grochowska, Alicja; Majewski, Jerzy (Studia Psychologica: Theoria et praxis, 2006)
The aim of this study was to show that a polygraph is a sensitive instrument measuring physiological reactions to advertisement (e.g. appealing to narcissism, aggressiveness, controversy and humour). 351 Ss took part in four studies. Physiological reactions were registered and analysed by the computer polygraph system Lafayette LX-3000W. The results indicate that advertisement appeals to narcissism, aggressiveness, controversy and humour elicit the physiological arousal. The meaning of application is discussed.